Russian VX: inhibition and reactivation of acetylcholinesterase compared with VX agent - Kuča, Kamil; Jun, Daniel; Cabal, Jiří; Hrabinová, Martina; Bartošová, Lucie; Opletalová, Veronika (Basic & clinical pharmacology & toxicology, 2006)
Organophosphorus compounds such as nerve agents inhibit, practically irreversibly, cholinesterases by their phosphorylation in the active site of these enzymes. Current antidotal treatment used in the case of acute nerve agent intoxications consists of combined administration of anticholinergic drug (usually atropine) and acetylcholinesterase (AChE, EC 3.1.1.7) reactivator (HI-6, obidoxime, pralidoxime), which from a chemical view is a derivative from the group of pyridinium or bispyridinium aldoximes (commonly called "oxime"). Oximes counteract acetylcholine increase, resulting from AChE inhibition. In the human body environment these compounds are powerful nucleophiles and are able to break down the bond between AChE and nerve agent molecule. This process leads to renewal of enzyme functionality -- to its reactivation. The usefulness of oxime in the reactivation process depends on its chemical structure and on the nerve agent whereby AChE is inhibited. Due to this fact, selection of suitable reactivator in the treatment of intoxications is very important. In our work, we have compared differences in the in vitro inhibition potency of VX and Russian VX on rat, pig and human brain, and subsequently we have tested reactivation of rat brain cholinesterase inhibited by these agents using oxime HI-6, obidoxime, pralidoxime, trimedoxime and methoxime. The results showed that no major differences in the reactivation process of both VX and Russian VX-inhibited cholinesterase. The similarity in reactivation was caused by analogous chemical structure of either nerve agent; and that oxime HI-6 seems to be the most effective reactivator tested, which confirms that HI-6 is currently the most potent reactivator of AChE inhibited by nerve agents. The results obtained in our study should be considered in the future development of new AChE reactivators.
Keywords: Swine; lidé; organothiofosforové sloučeniny; Rats; prasata; oximy; cholinesterasové inhibitory; Brain; Financing, Organized; Animals; Humans; Cholinesterase Inhibitors; reaktivátory cholinesterasy; Chemical Warfare Agents; zvířata; Cholinesterase Reactivators; chemické bojové látky; mozek; financování organizované; krysa rodu Rattus; Oximes; Organothiophosphorus Compounds